Using Social Media to Identify the Effects of Congressional Viewpoints on Asset Prices - Bianchi, Francesco; Gómez-Cram, Roberto; Kung, Howard (Review of Financial Studies, 2024)
Abstract We use a high-frequency identification approach to document that individual politicians affect asset prices. We exploit the regular flow of viewpoints contained in Congress members’ tweets. Supportive (critical) tweets increase (decrease) the stock prices of the targeted firm and the corresponding industry in minutes around the tweet. The bulk of the stock price effects is concentrated in the tweets revealing news about future legislative action. The effects are amplified around committee meeting days, especially when the tweet originates from committee members and influential politicians. Overall, we show that Congress members’ social media accounts are an important source of political news.